Pengaruh NAOH Dan HCL Terhadap Efisiensi Laju Korosi Pada Baja ASTM A36 Menggunakan Ekstrak Daun Ketapang (Terminalia Catappa.L) - Sinaga, Veranica; Komalasari, Komalasari; Heltina, Desi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Corrosion is damage or deterioration in the quality of a metal caused by reactions to the environment. Corrosion is a natural process that will never stop or will continue to occur as long as the metal material is in contact with its environment. However, the corrosion process can be controlled, minimized, or slowed down by the addition of an inhibitor. This research begins with the manufacture of ketapang leaf extract using the maceration method for 6 days with the volume ratio of ethanol-aquadest solvent (1: 4) The test method carried out in this research is the weight loss method by using variations in the concentration of Terminalia catappa. L leaf extract (0 and 2 g / L) with long soaking time (36, 48, 60 and 72 hours) in a corrosive solution of 1M HCl and 1M NaOH. The highest inhibition efficiency value in HCl corrosion media at 2 g / L inhibitor concentration with soaking time of 72 hours was 83.32%. Keywords: corrosion rate, inhibitor, Terminalia catappa. L leaf extract.